Haploidentical transplantation for acute myeloid leukemia patients with minimal/measurable residual disease at transplantation. Issue 12 (21st October 2019) - Srour, Samer A.; Saliba, Rima M.; Bittencourt, Maria C. B.; Perez, Jorge M. R.; Kongtim, Piyanuch; Alousi, Amin; Al‐Atrash, Gheath; Olson, Amanda; Betul, Oran; Mehta, Rohtesh; Popat, Uday; Hosing, Chitra; et al.
Abstract: There have been conflicting results regarding the impact of minimal/measurable disease at transplant on acute myeloid leukemia (AML) outcomes after haploidentical transplantation (haplo‐SCT). We assessed the impact of pre‐transplant disease status on post‐transplant outcomes of 143 patients treated with haplo‐SCT using fludarabine‐melphalan (FM) conditioning and post‐transplant cyclophosphamide (PTCy). With a median follow‐up of 29 months, the two‐year PFS for all patients was 41%. Compared to patients in complete remission (CR) at transplant, those with active disease (n = 29) and CR with incomplete count recovery (CRi) (n = 39) had worse PFS. They had hazard ratios (HR) of 3.5 (95% CI: 2.05‐6.1; P < .001) and 2.3 (95% CI: 1.3‐3.9; P = .002), respectively. Among patients who were in CR at transplant, there were no differences in PFS between those who had minimal residual disease (MRD) positive (n = 24), and MRD negative (n = 41) (HR 1.85, 95%CI: 0.9‐4.0; P = .1). In multivariable analysis for patients in CR, only age was predictive for outcomes, while MRD status at transplant did not influence the treatment outcomes. Our findings suggest that haplo‐SCT with FM conditioning regimen and PTCy‐based GVHD prophylaxis has a protective effect, and may potentially abrogate the inferior outcomes of MRD positivity for patients with AML. Patients with positive MRD may benefit from proceeding urgently to a haplo‐SCT, as this does not appear to negatively impact transplant outcomes.